Rural Livelihood in South-West Nigeria: Strategies, Assets Ownerships and the Non-Farm Income (2011)
The proliferation of Non-farm activities as a source of income to complement the once sole agricultural income in the rural part of Nigeria is an issue that calls for serious policy attention. It has been variously referred to as consumption smoothening measure or coping strategy against agricultural failure among other reasons. However, the fact remain that income from non-farm activities has become an integral part of the rural economy that requires empirical evaluation to enhance the emergence of a comprehensive agricultural and rural development plan in Nigeria. In view of this study assesses the livelihood strategies and the determinants of rural non-farm income in South-West Nigeria using a multi-stage random sample of 300 respondents. Descriptive statistics and multiple regressions were evaluated which confirmed the existence of non-farm activities alongside the farm activities despite the fact the respondents are still in their active working and productive age. Livelihood strategies in the area involve asset ownerships of both livestock and durable household assets. Common non-farm activities in the area are artisan, trade and commerce, etc which are mostly self-supervised and being funded through farm earnings. Non-farm activities have a higher profit level than the farming activities and such factors that determine its level of income are: Gender, household size, years of non-farm experience and exposure. Towards promoting such activities with policy instrument, attention must be paid to female-headed households, training and provision of vital information on highly profitable non-farm enterprises to the ruralites.